Financial resources support energy transition towards sustainable development in Vietnam - Vo , Xuân Vinh; Nguyen , Kim Chi; Vu , Minh Hà; Le , Huỳnh Như; Phan , Thị Hoàn (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This paper analyzes the critical role of financial resources in supporting the energy transition toward sustainable development in Vietnam. Amid global efforts to mitigate climate change, financial instruments such as green bonds and green credit have become pivotal in mobilizing capital for renewable energy projects. The study clarifies the role of Vietnam's financial system, from the activities of banks and financial institutions to international partnerships, in funding sustainable energy initiatives. Challenges such as limited financial tools, regulatory gaps, and the need for more comprehensive policies are also discussed. The paper proposes policy directions to enhance the capacity to attract and efficiently utilize financial resources, aligning with international standards and contributing to global climate goals.